Interactive Software Engineering Learning Environment - Ahmad, R.; Hin, K.W. (2007)
The main objective of most learning environments is to facilitate the process of learning and teaching. Components or features such as explanation, fast feedback and interaction, assessment and students adaptation are some of the features provided to support the process of learning. This paper describes one such learning environment which is designed to support software engineering course. This software engineering class is the third year course that covers main principles, techniques and methods of software development. Besides imparting and delivering software engineering knowledge, this course emphasize the development of software project which has to be implemented in a group. Hence, this learning environment uses experiential learning theory which provides a holistic model of the learning process as an approach for designing. It is designed to cater several important learning features as well as to support monitoring process for the instructor. This project is still ongoing in the department of Software Engineering, University Malaya.